Needs analysis in teaching learning process for developing teaching Arabic language syllabus of Islamic Religion Education of STAIS Sumatera - Surbakti, Andika Hariyanto (JOURNAL OF EDUCATION, 2015)
The study was aimed at describing: (1) the target needs of the students inlearning Arabic language of STAIS Sumatera, (2) the learning needs of the students in learning Arabic language of STAIS Sumatera, and (3) the development at the teaching Arabic language syllabus. The subjects of this study were 70 students of the semester 2 of Islamic religion education department of STAIS Sumatera in the academic year 2013/2014. The study consisted of data collection, data identiï¬ cation, data quantiï¬ cation, data description, and syllabus development. The Arabic teaching syllabus were developed based on the needs analysis data. The research instruments were questionnaires and interview guides. The results of the study are as follow. The target needs of the students of STAIS Sumatera in learning Arabic are to improve their Arabic language skills; the students' proï¬ ciency is in the elementary level;learning Arabic language is useful for their next career; the most popular topic is religion; the input is picture illustration; the learning activity is reading thenanswering comprehension questions; the teacher role is as a feedback giver; thelearners role is as active learners; and the setting is group work